Linguistic and Stylistic Means of Comic Effect Creation in Prose Text - An Educational Study - Blynova, Iryna; Breslavets, Nadiia; Repetii, Svitlana; Kovalenko, Borys; Diachuk, Liudmyla (Cadernos de Educação Tecnologia e Sociedade, 2024)
The article is dedicated to the study of linguistic and stylistic means of comic effect creation in English-language and French-language prose texts. The relevance of the study is stipulated by the constant interest of scientists in the phenomena of humour and its functioning in literary works. The research aims at the detection of linguistic and stylistic means for comic effect achievement in English-language and French-language prose texts. Study methods: descriptive method, comparative analysis, correlation analysis, quantitative analysis. Received results. Analysis of English-language and French-language prose texts found linguistic and stylistic means of comic effect on phonetic, lexical and pragmatic levels. Hyperbole, occasionalisms, allusion, similes, as well as devices such as irony, sarcasm, and paradox are widely used in two languages. The comic effect is the most evident at the lexical level. Conclusions drawn. Linguistic and stylistic means of comic effect creation have a universal nature. Nevertheless, their functioning varies in different languages and cultures, which affects the specifics of humour in English-language and French-language texts. The scientific novelty of the study. The novelty of the work lies in the attempt to systematise linguistic and stylistic means by which comic effect is created in English-language and French-language prose texts. Further study perspectives include a comparison of comic devices in different literary genres. The study of the comic at the intercultural level will enable a better understanding of cultural context and the effectiveness of means of humour in different cultures.